(3efGgL GdYbhd aj TQM efgGL GdCUhds - (3eMeO Hf GdMSf GdHONTis; (3GdHjVGhj , YHO Gddg Hf YeQ Hf eMeO Hf Ydj GdTjQGRj, fGUQ GdOjf CHh SYjO,J (B685 (3g` ? s
(3ChdgG (B:s
(3CeG HYO Ef cJGH efgGL GdhUhd Edi Yde GdCUhd s
(3BNQgG (B:s
(3bWH GdedI hGdOjf GdTjQGRi hgPG BNQ eG JjSQ ai eJf JMQjQ efgGL GdYbhd s
(3GdfSNI HgG MhGTs
(3hQO GdYfhGf GdCUdi ai cTa GdXfhf (B2/ 1878s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B97s
Keywords: (3CUhd Gdabgs